Use of Transcriptomics to Identify Candidate Genes for Hematopoietic Differences Between Wujin and Duroc Pigs - Peng Ji; Ping Wang; Qihua Li; Lin Gao; Yan Xu; Hongbin Pan; Chunyong Zhang; Jintao Li; Jun Yao; Qingcong An (Animals, 2024)
Hematopoiesis is a complex physiological process that ensures renewal of blood cells to maintain normal blood circulation and immune function. Wujin pigs exhibit distinct characteristics such as tender meat, high fat storage, strong resistance to roughage, robust disease resistance, and oxidation resistance. Therefore, using Wujin pigs as models may offer valuable insights for hematopoietic-related studies. In this study, twelve healthy 35-day-old piglets, including six Wujin and six Duroc piglets of similar weight, were selected from each of the Wujin and Duroc pig groups and housed in single cages. After 30 days of feeding, blood and bone marrow samples were collected. Routine blood indices and hematopoietic-related serum biochemical indexes of Wujin and Duroc pigs were determined, and bone marrow gene expression levels were analyzed using transcriptomics. (1) Hemoglobin (Hb) and Mean Corpuscular Hemoglobin Concentration (MCHC) levels in Wujin pigs were significantly higher than in Duroc pigs (p < 0.05), and platelet counts and serum Hb levels in Wujin pigs were significantly lower than in Duroc pigs (p < 0.05). (2) A total of 312 significantly differentially expressed genes were identified between the pigs. Their functions were mainly related to blood systems, inflammation, and oxidation. Six differentially expressed genes may be related to hematopoietic function. (3) By combining the differential genes screened through sequencing with Weighted Gene Co-expression Network Analysis results, 16 hematopoietic function differential genes were obtained, mainly focusing on immunity, inflammation, and induction of apoptosis functions. Differences were present in the immune and inflammatory responses between Wujin pigs and Duroc pigs, suggesting that differences in hematopoietic function between the two breeds were related to antioxidant capacity and disease resistance.